Analysis of The Effect of Liquidity, Leverage, and Size on Roa (Case Study of Telecommunication Companies Listed on The IDX for The 2017-2021 Period) - Nur Kamilah; Ratih Kusumawardhani; Alfiatul Maulida (PT SOLUSI EDUKASI BERDIKARI, 2024)
Analysis of the influence of liquidity, leverage, and size on return on assets (case study of Tbk Telecommunication Company 2017-2021) listed on the Indonesia Stock Exchange. Aims to answer the problem regarding the influence of liquidity, leverage and size on return on assets (case study of a telecommunications company). In this research the method used is a quantitative approach. The results of the research show that the variable current ratio (X1) has a significant influence on return on assets (Y). Then the cash ratio (X1) variable does not have a significant effect on return on assets (Y). Variable debt to equity ratio (X2) has a significant influence on return on assets (Y). And the size variable (X3) does not have a significant effect on return on assets (Y). And from the results of the f test it is proven that the current ratio, cash ratio, debt to equity, size have a simultaneous effect on return on assets (Y).